2015
DOI: 10.1126/sciadv.1500439
|View full text |Cite
|
Sign up to set email alerts
|

Nanodiamonds: The intersection of nanotechnology, drug development, and personalized medicine

Abstract: A method of developing new cancer therapies with nanodiamonds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
103
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 181 publications
(104 citation statements)
references
References 129 publications
0
103
0
1
Order By: Relevance
“…Sub-5 nm NPs such as NDs can be eliminated from the body renally without biodegradation and without leaving toxic residues. 588 However, larger inorganic NPs are more difficult to clear from the body. Studies have shown that AuNPs reside in macrophages after uptake and do not appear to be degraded; 589 ZnS-CdSe QDs have also been shown to remain stable in mice and rats after several months.…”
Section: In Vivo Treatment (“Particle-based Delivery”)mentioning
confidence: 99%
“…Sub-5 nm NPs such as NDs can be eliminated from the body renally without biodegradation and without leaving toxic residues. 588 However, larger inorganic NPs are more difficult to clear from the body. Studies have shown that AuNPs reside in macrophages after uptake and do not appear to be degraded; 589 ZnS-CdSe QDs have also been shown to remain stable in mice and rats after several months.…”
Section: In Vivo Treatment (“Particle-based Delivery”)mentioning
confidence: 99%
“…ND particles, which are capable of mediating improved efficacy and safety by forming complexes around the active agent while preserving its innate functionality (20)(21)(22)(23)(24)(25)(26)(27). ND safety and biocompatibility have been clearly demonstrated in numerous applications ranging from oncology to wound healing (28)(29)(30)(31)(32)(33)(34)(35).…”
Section: Significancementioning
confidence: 99%
“…Furthermore nanodiamonds are nontoxic cheap in production. Nanodiamonds have a greater biocompatibility and stable and easy to purify .There are ongoing researches on with doxorubicin attached nanodiamonds ( Ho et al, 2015). VNPs are one of the most advanced ad versatile nanomaterial produced by nature because of the highly symmetrical structure.…”
Section: Nanodiamondsmentioning
confidence: 99%